Labour of Love - Heleen Murre-van den Berg (ed) (Radboud University Press, 2025)
In this edited volume, publications from Armenian, Syriac, Coptic, and Tewahdo publishers are taken as crucial witnesses of how these communities rewrite themselves in the lands of migration, taking into account not only the texts as such, but also how physical books accompanied by social media and digital publications are central in a transnational religious practice geared towards transmitting tradition to the next generation. In this, the volume bridges the gap between two burgeoning fields, the anthropology of Orthodox Christianity and the historical study of the major texts that form the backbone of the Oriental religious traditions.